Effect of seeds roasting time on physicochemical properties, oxidative stability, and antioxidant activity of cactus (Opuntia ficus‐indica L.) seed oil. Issue 9 (23rd July 2021) - Nounah, Issmail; Gharby, Said; Hajib, Ahmed; Harhar, Hicham; Matthäus, Bertrand; Charrouf, Zoubida
Abstract: Cactus ( Opuntia ficus‐indica L.) seed oil, which is extracted from prickly pear fruit seeds, might constitute an alimentary source of substances of nutraceutical value. Physicochemical properties, chemical composition, antioxidant activity, and oxidative stability of prickly pear seed oil prepared from unroasted seeds were evaluated and compared with those of oil that was prepared from seeds roasted for different times. Prolonged roasting time had no significant influence on the protein content of the seeds. However, an increase in total phenolic compounds was observed from 225.9 mg GAE/100 g oil to 362.7 mg GAE/100 g oil after 40 min of roasting at 110℃. Consequently, an increase in antioxidant power which will induce a better oxidation resistance was found by the 1.1‐diphenyl‐2‐picrylhydrazyl method expressed as EC50 value that was reduced from 0.6 to 0.1 mg/ml. No significant change was observed in triacylglyceride and fatty acid composition, whereas tocopherol (512.8 to 542.1 mg/kg after 40 min of roasting) and sterol (8, 292 to 8, 629 mg/kg after 40 min of roasting) levels increased. Oxidative stability increased remarkably from 3.1 to 7.6 hr after 40 min of roasting with the increase in roasting time. The current study revealed that prickly pear seeds and the resulting oil have excellent nutritional qualities that were significantly elevated after roasting. Practical applications: Cactus seed oil is one of the most expensive vegetable oils and roasting of the seeds before pressing can help to improve not only the sensory quality of the oil but also the oxidative stability. Therefore, it is important to know more about the influence of roasting time on the quality of the oil. With this information, it is possible to optimize the roasting process regarding oil stability but also the release of bio‐active compounds such as tocopherols or phenolic compounds. Overall, this will significantly improve the acceptance of this oil.